Modernization of the Slavic and Mutual Communication (Philosophy of Sskepticism with Regard to Modern Globalization) - A. M. Petrovich (Vestnik MGIMO-Universiteta)
The article offers the rationale for the synthesis of Hegel's doctrine of the creative content of the movement absolute spirit of unity with the terms of philosophy of Vladimir Soloviev. In light of this synthesis have a limited positivist and phenomenological conceptions of existence. Analysis conducted by the author allows us to characterize as unacceptable and theoretically hopeless attempts of suppression of religious and cultural unity of the Slavic world by euroantlantic forces.